Implementasi Program Merdeka Belajar Kampus Merdeka Mahasiswa Fakultas Ilmu Sosial Universitas Negeri Padang - Fitra Novyan, Habif; Yusran, Rahmadani; Desyandri, Desyandri (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
Students from the Faculty of Social Sciences, Padang State University who take part in the MBKM program are the focus of this research which aims to analyze the implementation of MBKM program policies. This research specifically uses a qualitative descriptive approach. Interviews and documentation are the data collection tools used in this research. Data analysis includes data reduction methods, data presentation, and conclusion tracing. This research uses Grindle theory. which shows that the success of policy implementation is very dependent on existing interests. Based on research results, there are several MBKM programs that are participated in by social sciences faculty students as follows: Independent Student Exchange (PMM), Teaching Campus (KM), Indonesian International Mobility Awards (IISMA), Internships/Work Practices, aspects that help and hinder implementation MBKM program for students at the Faculty of Social Sciences, Padang State University.